Transcriptome analysis of Ochratoxin a (OTA) producing Aspergillus westerdijkiae fc-1 under varying osmotic pressure - Yanling Ma; Muyuan Zhuang; Tanvir Ahmad; Mingxuan Li; Guangyou Tan; Yingyao Deng; Yang Liu (Mycology)
Ochratoxin A (OTA) is a toxic secondary metabolite produced by the Aspergillus species which can contaminate various food products. This study analysed the transcriptome of the Aspergillus westerdijkiae fc-1 strain under NaCl concentrations of 0, 20, and 100 g/L using RNA-Seq technology to examine gene transcriptional changes linked to osmotic stress and OTA production. Significant changes were observed in metabolic-pathways associated with carbohydrates, cellular communication, and hydrolase activity under 20 g/L NaCl. The HOG1 gene, associated with osmotic pressure regulation was down-regulated by 78.06%. In contrast, OTA biosynthesis genes otaA, otaB, and otaC were up-regulated by 3.26 fold, 1.99 fold, and 2.06 fold, respectively. Conversely, the otaD gene was down-regulated by 43.50%. At 100 g/L NaCl, pathways related to ion transport, peptide metabolism, ribosomal function, and transmembrane transporter protein activities were significantly up-regulated. The HOG1 gene was up-regulated by 28.32% and OTA biosynthesis genes otaA, otaB, otaC, and otaD showed up-regulation of 27.06%, 36.80%, 19.59%, and 5.72 fold, respectively. The study highlights the role of metabolic pathways in osmotic stress regulation and the correlations between HOG1 expression and OTA biosynthesis genes, providing insights for developing strategies to prevent OTA contamination in food.